Exploring the influence of shapes and heterogeneity of glyco-gold nanoparticles on bacterial binding for preventing infections - Toraskar, Suraj; Gade, Madhuri; Sangabathuni, Sivakoti; Thulasiram, Hirekodathakallu V.; Kikkeri, Raghavendra (Chemmedchem, 2017)
To investigate the effects of the heterogeneity and shape of glyco-nanoprobes on carbohydrate-protein interactions (CPIs), alpha-d-mannose-and beta-d-galactose-linked homo-and heterogeneous glycodendrons were synthesized and immobilized on spherical and rod-shaped gold nanoparticles (AuNPs). Lectin and bacterial binding studies of these glyco-AuNPs clearly illustrate that multivalency and shape of AuNPs contribute significantly to CPIs than the heterogeneity of glycodendrons. Finally, bacterial infection of HeLa cells was effectively inhibited by the homogeneous glycodendron-conjugated rod-shaped AuNPs relative to their heterogeneous counterparts. Overall, these results provide insight into the role of AuNP shape and multivalency as potential factors to regulate CPIs.